New antimicrobials and plant defense inducers for managing citrus canker disease - Kunwar, Sanju; Redondo, Ana; Manker, Denise; Iott, Meagan; Knobloch, Thomas; Brunet, Stéphane; Dufour, Jeremy; Batuman, Ozgur (Frontiers in Agronomy, 2023)
For over two decades, Florida citrus growers have been heavily using copper sprays to combat citrus canker (Xanthomonas citri subsp. citri; Xcc), but it raises the risk of developing resistant bacterial strains and excessive accumulation in the soil. Alternative methods are needed to reduce copper dependency and better manage Xcc. Therefore, we screened copper-alternative products against canker on young seedlings in the greenhouse and mature trees in a commercial grove in Florida, USA. In the greenhouse, we evaluated the efficacy of single foliar application of new plant defense inducers (PDI), 'PDI5', 'PDI26', and 'PDI31', and a commercially available systemic acquired resistance inducer, Actigard (drench; 2g/tree), applied two days before injection-infiltration with citrus canker bacterium Xcc, on two-year-old Valencia trees. All three PDIs, sprayed at 500 ppm, as well as Actigard (drench), effectively reduced canker severity on the inoculated leaves in the greenhouse (P ≤0.02). In the grove, we tested new antimicrobials, Mastercop 'MC', 'AM', and a nutrient solution (AGRO-MOS) for canker suppression on 4-6-year-old Hamlin trees. Kocide 2000 (growers' standard control) was used as a control check. Although 2021 was not as conducive for citrus canker due to the relatively dry spring months in the field, our results showed that the six sprays of AM or MC, in 2022, provided excellent control of Xcc, with a significant reduction in disease incidence in leaves and fruits, and disease severity in fruits, similar to Kocide 2000. The results indicate that antimicrobials, AM and MC, and plant defense inducers PDI5, PDI26, and PDI31 can be part of an integrated pest management (IPM) program with copper for managing citrus canker. Reducing the frequency and amount of copper applications can help reduce pesticide and application expenses, lower risks of copper buildup in the soil and toxicity for citrus trees and reduce the risk of the emergence of copper-resistant Xcc strains. Further research on these products is needed to assess their long-term effectiveness and potential environmental risks.